Utilising journaling technique to enhance creative writing skills among primary school students - Dayangku Nurhanis Awangku Arni,; Azlina Abdul Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Academic writing has received greater attention in research studies concerning ESL writing than creative writing. However, there are still limited studies on journal writing as one of the strategies for enhancing creative writing skills. This study’s primary goal is to provide an insight into Year 5 students’ perspectives on journal writing in which they kept open-ended journals for twelve weeks. This study used a semi-structured interview in conjunction with mixed-methods research. To analyse the data, the researcher used descriptive analysis to identify the frequency of each theme. The results reveal that the advantages, difficulties and variables impacting ESL students’ creative writing skills are more widely discussed in relation to journal writing. According to the research findings, students who journal on a daily basis start to reflect on their lives and make efforts to improve their writing skill as well as creative writing. Furthermore, the review signifies the development of a number of assistance measures for students to enhance their creative writing skills through journaling. In summary, there are certain difficulties in utilising journaling strategy to enhance creative writing skills among primary school students; nonetheless, the benefits of the research greatly exceed these difficulties.